A QUALITATIVE STUDY OF CREATIVE LEADERSHIP AND SCHOOL PERFORMANCE - Cucuk Kristiono; Olivia Fachrunnisa (UNISSULA, 2017)
The success of school performance is influenced by teachers and staff performance, whereas teacher and staff accomplishment is affected by principals’ leadership styles. This paper aims to observe principals’ ideal leadership styles and their impacts on school performance and staff performance. This study used qualitative method with phenomenological approach. The object of the study was principals’ leadership styles which were perceived by administration staff and teachers. 30 interviewees were involved in this study which consisted of 5 principals, 20 teachers, and 5 school staffs. Based from the data, this study found that creative leadership was perceived as the best style to manage good relationship within school staffs. Morever, there were five basic foundations of leadership behaviours that could be used to intervene leadership styles. The principal encouraged staff creativities through reflection of principal behaviors such as, being role models, commitment building, striving to accomplish vision and mission together .Keywords: Creative leadership, school performance, teacher and administration staff